Belief Dispersion and Convex Cost of Adjustment in the Stock Market and in the Real Economy - Jouini, Elyès (Management Science, 2023)
I develop a continuous-time general equilibrium model with a continuum of states of the world and a continuum of agents endowed with heterogeneous beliefs. The model permits to analyze the interactions between financial markets and production. There is a single firm that faces convex adjustment costs and maximizes its terminal value. Equivalently, the firm uses decreasing returns to scale risk-return technology. The model is tractable and matches many of the empirical regularities in aggregate output and stock prices, such as a financial volatility that is higher than the macroeconomic volatility, skewness, kurtosis, short-term momentum, and volatility risk premium during recessions. All these aspects disappear when one assumes beliefs homogeneity or constant returns to scale. In particular, the impact of beliefs heterogeneity observed in endowment economies does not pertain when introducing production unless one assumes decreasing returns to scale in the risk-return technology. This paper was accepted by David Sraer, finance. Supplemental Material: The online appendix is available at https://doi.org/10.1287/mnsc.2022.4495 .